Experiences of "openness" between mothers and daughters during breast cancer: implications for coping and healthy outcomes. Issue 11 (20th September 2016) - Fisher, Carla L.; Wolf, Bianca M.; Fowler, Craig; Canzona, Mollie Rose
Abstract: Objective: Mother‐daughter communication is central to how women adjust to breast cancer. They may be aided by models of healthy communication that illustrate both women's perspectives. Families establish normative communication patterns that inform how they cope. We used family communication patterns theory to examine correlations between openness/avoidance and health. We extended this by capturing mother‐daughter open/avoidant narratives to illustrate how these behaviors function in helpful (health‐promoting) and unhelpful ways. Methods: Phase 1 of this mixed‐method study involved 41 patients and 37 mothers/daughters ( N  = 78) completing surveys on mother‐daughter openness, avoidant coping, and quality of life. Phase 2 involved interviews with 40 patients and 38 mothers/daughters ( N  = 78) to ascertain what diagnosed women share (or do not share) with their mother/daughter and their reasons. Results: Diagnosed women reporting more open mother‐daughter bonds had better relational health ( r  = .730, P <  .001). Those who engaged in more avoidant coping reported poorer physical health ( r  = −.431, P  = .01). Mothers and daughters talked about treatment side effects and procedures, disease risk and prevention, and medical decisions. They avoided discussions about distressing emotions and topics as well as uncertainty about the future. Motivations to disclose/avoid centered on protecting themselves and/or their mother/daughter. Qualitative findings illustrate the tension between openness and avoidance. Developmental differences and relational role perspectives illustrate women's diverse needs. Conclusions: A history of openness is linked with relational health, but coping is not as simple as "be open." Both openness/avoidance are helpful and unhelpful depending on age, topic, and responses.